ASCE issues in engineering. - American Society of Civil Engineers ([New York] American Society of Civil Engineers, 1979)
"Journal of professional activities; proceedings of the American Society of Civil Engineers."
Keywords: Civil engineering -- Periodicals; Civil engineers -- United States -- Periodicals; Civil engineering